Examining arts education policy development through policy frameworks. Issue 4 (2nd October 2019) - Shaw, Ryan D.
ABSTRACT: While policy formation frameworks are commonly used to understand public policy developments, scholars rarely have used them to reflect on arts education policies. Such analysis is important because it can assist both in identifying the genesis of past policies, including who the important actors are, how issues are framed and problematized, and how specific solutions are designed, as well as how to interpret unfolding policies. In this article, I review three prominent policy frameworks: Kingdon's "multiple streams framework, " Sabatier and Jenkins-Smith's "advocacy coalition framework, " and Baumgartner and Jones' "punctuated equilibrium framework." After reviewing the frameworks, I address the following questions: (a) How would these conceptual frameworks predict arts education policy development to proceed? (b) How would these conceptual frameworks explain constituents and coalitions that affect the arts education policy sphere? (c) How would these conceptual frameworks illuminate precipitating events that drive the policy development process? I apply the frameworks to several instances of arts education policy development, including the formal designation of the arts as a core subjects under the Goals 2000: Educate America Act of 1994 (P.L. 103-227), the development of the 2014 National Core Arts Standards, and music's enumeration in the Every Student Succeeds Act of 2015. Because these three policy issues differ in important ways, they can help to illuminate the breadth of arts education policy.